2008
DOI: 10.1016/j.drugalcdep.2007.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gabapentin on cocaine self-administration, cocaine-triggered relapse and cocaine-enhanced nucleus accumbens dopamine in rats

Abstract: Gabapentin is a γ-aminobutyric acid (GABA) analogue, with GABAmimetic pharmacological properties. Gabapentin is used for the treatment of seizures, anxiety and neuropathic pain. It has been proposed that gabapentin may be useful in the treatment of cocaine dependence. However, clinical trials with gabapentin have shown conflicting results, while preclinical studies are sparse. In the present study, we investigated the effects of gabapentin on intravenous cocaine self-administration and cocaine-triggered reinst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 55 publications
2
21
0
3
Order By: Relevance
“…failed to inhibit i.v. cocaine self-administration under FR2 reinforcement or cocaine-triggered reinstatement of cocaine-seeking behavior in rats [170]. Congruent with our findings, Filip et al .…”
Section: Gaba-based Medication Discoverysupporting
confidence: 89%
“…failed to inhibit i.v. cocaine self-administration under FR2 reinforcement or cocaine-triggered reinstatement of cocaine-seeking behavior in rats [170]. Congruent with our findings, Filip et al .…”
Section: Gaba-based Medication Discoverysupporting
confidence: 89%
“…Di Matteo et al (2000) showed that administration of Amt also increased dopamine release in the rat NAc, suggesting the possible involvement of serotonin 5HT 2C receptors. Peng et al (2008), in turn, failed to demonstrate any alteration of the dopamine level within the NAc using Gb or even after cocaine selfadministration, cocaine-triggered relapse and cocaineenhanced NAc dopamine in rats. Our results suggest that drugs which, according to previous studies, exhibit the capacity of increasing dopamine concentrations in the NAc, such as Amt, Me and Mo, also induced an increased GFAP immunoreactivity in this region, probably by enhancing the astrocyte activity of clearing excess dopamine.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanism for these behavioral effects has long been thought to be GVG-enhanced extracellular GABA with consequent inhibition of addictive drug-induced increases in extracellular dopamine (DA) in the nucleus accumbens (NAc) (Dewey et al 1997; Morgan and Dewey 1998; Schiffer et al 2000). Contrary to this view, we have recently reported that GVG or gabapentin, whether administered systemically or locally into the NAc, fails to alter either basal or cocaine-enhanced extracellular DA (Peng et al 2008a,b), suggesting that a non-DA mechanism may underlie the action of GVG or gabapentin in animal models of drug addiction (Peng et al 2008a, b; Xi and Gardner 2008). …”
Section: Introductionmentioning
confidence: 73%